PEMBERDAYAAN MASYARAKAT DESA DALAM MENGEMBANGKAN EKONOMI KREATIF DI DESA CITENGAH KABUPATEN SUMEDANG - Ridwan Ridwan; Catur Surya (JRAK, 2018)
Creative economic development in Citengah Village seeks to 1) realize the potential of nature and exploit it maximally and develop the character of the villagers through the art community, 2) improve the human resources of the local villagers. Many of the natural wealth besides the natural tourist destinations also have other natural potentials to be developed into goods of economic value, as well as woven handicrafts, handicrafts from leaves or jepal bark (upih). To uncover and discuss such problems using methods, interviews, literature studies, field studies, and experiential experiences as part of the village community of Citengah Kabupaten Sumedang. The results show that the social characteristics and skills significantly show positive things. At the end, goal is able to create and empower the natural wealth of more economic value in addition to the value and cultural richness.